2021
DOI: 10.1111/tme.12790
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non‐point‐of‐care haemostasis management protocol implementation in cardiac surgery: A systematic review

Abstract: Objectives This systematic review aims to outline the evidence on the implementation of a non‐point‐of‐care (non‐point‐of‐care [POC]) haemostasis management protocol compared to experience‐based practice in adult cardiac surgery. Background Management of coagulopathy in cardiac surgery is complex and remains highly variable among centres and physicians. Although various guidelines recommend the implementation of a transfusion protocol, the literature on this topic has never been systematically reviewed. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The risk of bleeding complications in paediatric cardiac surgery is exacerbated by complex operations in low-weight children with an undeveloped coagulation system. Early detection and characterisation of the coagulopathy using TEM/TEG will maximise the chance for early treatment of haemostatic abnormalities if bleeding occurs [24,25]. Paediatric cardiac surgery research using TEM/TEG revealed that patients with congenital heart disease have defective clot formation, especially in children with cyanotic heart disease.…”
Section: Causes Of Coagulopathymentioning
confidence: 99%
“…The risk of bleeding complications in paediatric cardiac surgery is exacerbated by complex operations in low-weight children with an undeveloped coagulation system. Early detection and characterisation of the coagulopathy using TEM/TEG will maximise the chance for early treatment of haemostatic abnormalities if bleeding occurs [24,25]. Paediatric cardiac surgery research using TEM/TEG revealed that patients with congenital heart disease have defective clot formation, especially in children with cyanotic heart disease.…”
Section: Causes Of Coagulopathymentioning
confidence: 99%